1998
DOI: 10.1021/bi980273v
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Context Profoundly Influences the Mutagenic Potency of Trans-Opened Benzo[a]pyrene 7,8-Diol 9,10-Epoxide−Purine Nucleoside Adducts in Site-Specific Mutation Studies

Abstract: The postoligomerization method was used to prepare oligonucleotide 16-mers that contained dAdo or dGuo adducts, derived from trans opening of each enantiomer of the two diastereomeric benzo[a]pyrene 7,8-diol 9,10-epoxides, in two sequence contexts. These 16 oligonucleotides, along with the four corresponding oligonucleotides containing unsubstituted purines, were ligated into single-stranded DNA from bacteriophage M13mp7L2 and transfected into Escherichia coli SMH77. The mutagenic effects of replication past t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
146
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(154 citation statements)
references
References 44 publications
7
146
1
Order By: Relevance
“…The guanine base may have to shift toward the minor groove (33), thus inducing mispairing with dT or dA. In support of this hypothesis, it has been reported that, depending on the sequence context, BPDE-dG adducts induce either G 3 A or G 3 T mutations (30,31).…”
Section: Figmentioning
confidence: 88%
See 1 more Smart Citation
“…The guanine base may have to shift toward the minor groove (33), thus inducing mispairing with dT or dA. In support of this hypothesis, it has been reported that, depending on the sequence context, BPDE-dG adducts induce either G 3 A or G 3 T mutations (30,31).…”
Section: Figmentioning
confidence: 88%
“…The unusually small finger and thumb domains of the Y-family polymerases leave the major and minor groove wide open (26)(27)(28)(29) and thus may facilitate such adduct placement. The crystal structure, although representing primer extension beyond the dA* lesion, offers insights into how base substitution and frameshift mutations are induced by BPDE adducts at dA and dG (30)(31)(32). When the PAH is placed in the major groove in the BP-2 complex, the adenine base of the dA* shifts Ϸ2 Å toward the major groove, juxtaposing two hydrogen bond acceptors, the N1 of dA* and the O 4 of its base pair partner dT (Fig.…”
Section: Figmentioning
confidence: 99%
“…1A) were prepared from the mixed 10R/ 10S diastereomers of the BaP DE dG phosphoramidite (20) and were separated by reverse-phase high-performance liquid chromatography. Their absolute configurations were assigned from the long-wavelength CD spectra of the separated oligonucleotides, which exhibit positive bands in the 330 -360 nm region for the 10R adduct and negative bands for the 10S adduct (21). All other adducted oligonucleotides were prepared from diastereomerically pure 10R or 10S phosphoramidites derived from the 10R and 10S diastereomers of the BaP DE dG adducts that had been separated as their O 6 -allyl di-tert-butyldimethylsilyl triacetates (22).…”
Section: Methodsmentioning
confidence: 99%
“…Oligonucleotides-Oligonucleotides containing a single specific cis or trans BaP DE-2 dG adduct placed on the fourth nucleotide from the 5Ј-end in either sequence context III(G) (5Ј-TTCG*AATCCTTCCCCC-3Ј) or IV(G) (5Ј-GGGG*TTCCCGAGCGGC-3Ј) were synthesized as described previously (29,30). The basis for selection of these sequences has been described previously (30).…”
Section: Methodsmentioning
confidence: 99%